Budaya Kerja Era New Normal: Saatnya Merubah Paradigma (Studi pada UKM di Malang Raya) - Halid Hasan; Farika Nikmah; Heru Utomo; Erlangga Andi Sukma; Ellyn Eka Wahyu (Syntax Literate, 2022)
SMEs have been severely impacted by the Covid-19 pandemic. Some changes or adaptations need to be made to follow the changes that occur. Action research was chosen in this study, using the planning, implementation and evaluation method, where the samples were culinary SMEs, several cafes in Malang Raya. The planning stage involves identifying the problems and obstacles faced by SMEs, through interviews using an interview guide, then from this stage a strategy formulation is obtained which is implemented at the implementation stage. Adopting the work culture proposed by Denison and Haaland, a new work culture strategy is formulated to deal with the new normal era. Mission, involvement, adaptation and consistency are used as indicators at the implementation stage. Then proceed with an evaluation to measure the level of success of research in contributing to the sustainability of SMEs in running their business. SMEs are no longer run at random, but with careful planning to minimize product failures, maintain business sustainability and even win in the face of business competition both with fellow SMEs and with companies.